miR-18a-5p Is Involved in the Developmental Origin of Prostate Cancer in Maternally Malnourished Offspring Rats: A DOHaD Approach - Santos, Sergio Alexandre Alcantara [UNESP]; Portela, Luiz Marcos Frediani [UNESP]; Camargo, Ana Carolina Lima [UNESP]; Constantino, Flavia Bessi [UNESP]; Colombelli, Ketlin Thassiani [UNESP]; Fioretto, Matheus Naia [UNESP]; Mattos, Renato [UNESP]; de Almeida Fantinatti, Bruno Evaristo [UNESP]; Denti, Michela Alessandra; Piazza, Silvano; Felisbino, Sérgio Luis [UNESP]; Zambrano, Elena; et al. (MDPI, 2022)
The Developmental Origins of Health and Disease (DOHaD) concept correlates early life exposure to stressor conditions with the increased incidence of non-communicable chronic diseases, including prostate cancer (PCa), throughout the life span. However, the molecular mechanisms involved in this process remain poorly understood. In this study, the deregulation of two miRNAs (rno-miR-18a-5p and rno-miR-345-3p) was described in the ventral prostate VP of old rats born to dams fed with a low protein diet (LPD) (6% protein in the diet) during gestational and lactational periods. Integrative analysis of the (VP) transcriptomic and proteomic data revealed changes in the expression profile of 14 identified predicted targets of these two DE miRNAs, which enriched terms related to post-translational protein modification, metabolism of proteins, protein processing in endoplasmic reticulum, phosphonate and phosphinate metabolism, the calnexin/calreticulin cycle, metabolic pathways, N-glycan trimming in the ER and the calnexin/calreticulin cycle, hedgehog ligand biogenesis, the ER-phagosome pathway, detoxification of reactive oxygen species, antigenprocessing-cross presentation, RAB geranylgeranylation, collagen formation, glutathione metabolism, the metabolism of xenobiotics by cytochrome P450, and platinum drug resistance. RT-qPCR validated the deregulation of the miR-18a-5p/P4HB (prolyl 4-hydroxylase subunit beta) network in the VP of older offspring as well as in the PNT-2 cells transfected with mimic miR-18a-5p. Functional in vitro studies revealed a potential modulation of estrogen receptor α (ESR1) by miR-18a-5p in PNT-2 cells, which was also confirmed in the VP of older offspring. An imbalance of the testosterone/estrogen ratio was also observed in the offspring rats born to dams fed with an LPD. In conclusion, deregulation of the miR-18a-5p/P4HB network can contribute to the developmental origins of prostate cancer in maternally malnourished offspring, highlighting the need for improving maternal healthcare during critical windows of vulnerability early in life.
Keywords: aging; Developmental Origins of Health and Disease (DOHaD); epigenetics; miR-18a-5p/P4HB network; prostate cancer